Bricolage w wykorzystaniu zasobów społecznych wsi. Relacja między zasobami społecznymi obszarów partnerstw a kapitałem społecznym lokalnych grup działania z województw o odmiennych tradycjach społecznikowskich = Bricolage in the use of social resources of rural areas. Ther elation between social resources of partnerships and social capital of local action groups from provinces with varied social activist traditions. - Zajda, Katarzyna (PAN IGiPZ, 2017)
The issue of social activist traditions impact on different features of contemporary societies, institutions and organizations, for example their social capital, has been discussed in the relevant literature. The subject of this paper is the relation between level of social resources in the areas in which local action groups’ work (in provinces with historically varied social activist traditions, i.e. the Western and Northern Territories, on the one hand, and Galicia and Greater Poland, on the other hand) and their social capital. The aim of the article is to find the answers to the following questions: Does the location of those organisations in provinces with historically varied social activist traditions determine their different access to social resources? Do the deficits of social resources in the areas supported by those organisations have a negative influence on their social capital? In order to find the answers to these questions, 287 survey questionnaires filled in by members of 18 local action groups were analysed. All the questions were answered negatively. The findings were interpreted with reference to the concept of bricolage, which showed it from a new perspective.
24 cm
Keywords: social capital; social resources; Local Action Groups; historical regions of Poland; bricolage